2021
DOI: 10.3390/jcm10214865
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping and Life Satisfaction during the COVID-19 Pandemic among Polish Catholics. The Mediating Effect of Coronavirus Anxiety

Abstract: Recent data have indicated that people may have experienced fear during the COVID-19 pandemic. This study aims to deepen our understanding of the relationship between religious coping and life satisfaction by analysing the indirect effects of fear of COVID-19. Methods: This study included 365 people (75% women) aged 18–78 years. The procedure consisted of completing questionnaires to measure religious coping, COVID-19 anxiety, satisfaction with life, and satisfaction with social support. Results: Structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 110 publications
(145 reference statements)
2
12
0
2
Order By: Relevance
“…In addition, we observed associations of religiosity and spirituality with religious coping, well-being, and life satisfaction, which is a common observation in the literature ( 29 , 69 ). We have also shown that both spirituality and religiosity are positively associated, to some extent, with perceptions of nature and silence.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, we observed associations of religiosity and spirituality with religious coping, well-being, and life satisfaction, which is a common observation in the literature ( 29 , 69 ). We have also shown that both spirituality and religiosity are positively associated, to some extent, with perceptions of nature and silence.…”
Section: Discussionsupporting
confidence: 72%
“…Anxiety, a sense of being burdened, and stress are common responses to perceived or real threats, and also when faced with uncertainty or the unknown. So, it is understandable that people feel such tension in the context of the COVID-19 pandemic [1][2][3][4]. In addition to the fear of contracting the virus, there are significant changes in everyday life, as individuals are restricted in their functioning as part of efforts to contain and slow down the spread of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Before making broader generalizations, though, it is important to consider some limitations in the analyses conducted. First, the sample consisted primarily of Catholics (according to the Central Statistical Office—GUS—in Poland, approximately 85% of the population is Catholic; [ 55 ]). In such a situation, the effect of the influence of religion (not significant in our study) may be underestimated.…”
Section: Discussionmentioning
confidence: 99%